2003
DOI: 10.1177/000348940311201111
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology of the Inner Ear in Unoperated Acoustic Neuroma

Abstract: Although hearing loss is the most common presenting symptom in patients with acoustic neuroma, the pathophysiology of hearing loss associated with acoustic neuroma is unknown. Although primary dysfunction of the auditory nerve is intuitively logical, available histopathologic and clinical data suggest that although neural degeneration is common, it alone does not adequately account for hearing loss in many cases. The purpose of this study was to evaluate 11 cases of unoperated unilateral acoustic neuromas. Tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 18 publications
1
71
0
Order By: Relevance
“…17 A recent histopathological study of unresected unilateral acoustic neuromas showed that degenerative changes in the inner ear and atrophy of the stria vascularis and spiral ligament were present in addition to cochlear nerve degeneration when compared with control specimens. 17 Tumor adherence to the cochlear nerve in the IAC 3 as well as increases in IAC pressure from tumor 13 may be responsible for these changes, which have been shown to adversely affect hearing outcome.…”
Section: Hearing Preservationmentioning
confidence: 99%
“…17 A recent histopathological study of unresected unilateral acoustic neuromas showed that degenerative changes in the inner ear and atrophy of the stria vascularis and spiral ligament were present in addition to cochlear nerve degeneration when compared with control specimens. 17 Tumor adherence to the cochlear nerve in the IAC 3 as well as increases in IAC pressure from tumor 13 may be responsible for these changes, which have been shown to adversely affect hearing outcome.…”
Section: Hearing Preservationmentioning
confidence: 99%
“…The significance of ELH in the development of symptoms in patients with MD has been recognized by many investigators, and the histological finding of Reissner's membrane distension is taken to be the hallmark of ELH (Arenberg et al, 1970;Belal and Ylikoski, 1980;Fraysse et al, 1980;Paparella, 1984;Schuknecht, 1976). However, ELH occurs in conditions other than Meniere's disease, including delayed endolymphatic hydrops following trauma (Dodson et al, 2007), relapsing polychondritis (Murata et al, 2006), and some cases of acoustic neuroma (Mahmud et al, 2003). Unfortunately, current therapies directed at alleviating symptoms via presumed amelioration of ELH using diuretics and shunt surgery have been largely unsuccessful in preventing the progression of hearing deterioration in patients with ELH-related disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The factors that make the final decision a daunting task include variability in the data on the natural history of VS, 68,86,118 mechanism of hearing loss, 27,37,57,81,99 and treatment-specific hearing and facial function preservation rates. 96,98,101 These inconsistencies are a major hindrance to the practice of evidence-based medicine.…”
Section: What Actually Creates the Treatment Dilemma?mentioning
confidence: 99%